Determination of platinum, palladium, rhodium and gold in platiniferous ores using ICP-MS and microwave dissolution - Matsau, Eunice Nthabiseng (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2003.